2020
DOI: 10.2147/ott.s229055
|View full text |Cite
|
Sign up to set email alerts
|

<p>DEP Domain-Containing Protein 1B (DEPDC1B) Promotes Migration and Invasion in Pancreatic Cancer Through the Rac1/PAK1-LIMK1-Cofilin1 Signaling Pathway</p>

Abstract: Background: With increasing incidence, pancreatic cancer (PC) is one of the most common digestive tract tumors. However, the prognosis of PC is particularly dismal due to the highly invasive and metastatic behavior of this deadly disease. DEP domain-containing protein 1B (DEPDC1B), which is overexpressed in multiple tumors, such as breast cancer, oral cancer and non-small cell lung cancer, plays a significant role in cell movement, cell cycle and cytoskeleton reorganization. However, the function of DEPDC1B in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
0
17
1
Order By: Relevance
“…More recently, it was demonstrated that the KD of DEPDC1B inhibits the occurrence of malignant melanoma by inhibiting cell proliferation and inducing cell apoptosis 26 . Moreover, DEPDC1B was found to be able to promote migration and invasion of pancreatic cancer through Rac1/PAK1-LIMK1-Cofilin1 signal pathway 28 . However, the understanding of the relationship between DEPDC1B and human cancers and the underlying mechanism was still in shortage.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, it was demonstrated that the KD of DEPDC1B inhibits the occurrence of malignant melanoma by inhibiting cell proliferation and inducing cell apoptosis 26 . Moreover, DEPDC1B was found to be able to promote migration and invasion of pancreatic cancer through Rac1/PAK1-LIMK1-Cofilin1 signal pathway 28 . However, the understanding of the relationship between DEPDC1B and human cancers and the underlying mechanism was still in shortage.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, DEPDC1B is required for a variety of malignancies, such as breast cancer [ 11 , 16 ], non-small cell lung cancer [ 17 ], oral cancer [ 18 ], prostate cancer [ 19 ], melanoma [ 20 ], and glioblastoma [ 21 ]. In pancreatic cancer or prostate cancer, DEPDC1B could promote migration and invasion through Rac1/PAK1 signaling [ 22 , 23 ]. In bladder cancer, DEPDC1B is a tumor promotor through targeting SHC1 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A reverse transcription system was used to obtain the first-strand template Complementary DNA (cDNA). The primer sequences were used as follows: DEPDC1B: 5′- GAG​CTA​CCA​GGC​TGT​GGA​AT-3′ (forward) and 5′- GCC​GAA​GTT​TTG​ACT​GCA​CC -3′ (reverse); GAPDH: 5′-CCATGTTCGTCATGGGTGTGAACCA-3′(forward) and 5′-GCCAGTAGAGGCAGGGATGATGTTC-3′(reverse) ( Li et al, 2020 ; Zhang et al, 2020 ). The expression of GAPDH was considered as an internal control.…”
Section: Methodsmentioning
confidence: 99%